Systematic Review of Worldwide Infant Blood and Human Milk Carotenoid Concentrations. (14th June 2022) - Moran, Nancy; Stroh, Rachel; Zaidi, Yusuf
Abstract: Objectives: Dietary carotenoids may support infant vitamin A status, and cognitive and visual functions, but infant carotenoid exposures are not well defined. The purpose of this study is to address a knowledge gap in worldwide estimates of human milk and infant blood carotenoid concentrations across lactation and feeding stages, respectively. Methods: Systematic searches of articles describing infant blood and human milk carotenoid concentrations in healthy populations were conducted in three databases. Concentration data from healthy participants not currently receiving a carotenoid intervention, for which the postpartum time of collection was clear, and measurements were acquired by HPLC were included for analysis. Mean ± 95% confidence intervals of infant blood (serum/plasma) carotenoid species concentrations were calculated within feeding stage [newborn, exclusive milk feeding (<6 mo), complementary feeding (6–12 mo)], and by milk type (human milk, infant formula); and human milk carotenoid species concentrations were calculated by lactation stage [colostrum (<5 d), transitional (5–14 d), and mature (>14 d)]. Results: Infant blood carotenoid concentrations came from 47 articles published from 1989–2021. An array of major dietary carotenoids are observed in infant blood across newborn, exclusively human milk-feeding, and complementary feeding stages, with more abundant species being beta-carotene (6.1 ± 3.7,  15.7 ± 8.5,  5.7 ± 2.9 ug/dL), lutein (3.6 ± 1.1,  9.7 ± 2.7,  9.9 ± 2.3 ug/dL), and lycopene (2.0 ± 0.4,  7.7 ± 2.7,  5.4 ± 1.6 ug/dL), respectively. Human milk carotenoid data came from 65 articles, published from 1994–2020. An array of major carotenoids are observed in human milk, with more abundant species in colostrum, transitional, and mature milk being beta-carotene (18.4 ± 2.8,  6.9 ± 3.3,  2.5 ± 0.5 ug/dL), lutein (14.6 ± 2.6,  9.1 ± 1.1,  5.7 ± 0.6 ug/dL), beta-cryptoxanthin (20.1 ± 4.8,  3.3 ± 0.4,  3.1 ± 0.9 ug/dL) and lycopene (26.9 ± 5.9,  2.9 ± 0.5,  2.4 ± 0.3 ug/dL), respectively. Conclusions: Infants are exposed to an array of major dietary carotenoids. These population estimates of milk and infant blood carotenoid concentrations can be used to contextualize research findings and to design nutritionally relevant carotenoid interventions to study the role of carotenoids in infant nutrition and health. Funding Sources: USDA/ARS CRIS3092-51, 000-059-NEW2S.